Karakteristik Kepemimpinan Kepala Sekolah di Ma Al-Ma’arif Kubu Raya - Muhammad Amrozi Ma’arif; Samiyah (CV Putra Publisher, 2024)
This study aims to describe the characteristics of principal leadership at MA Al-Ma'arif. The approach used is qualitative with a case study method. The researcher acts as the main instrument in data collection, which is carried out through in-depth interviews, participant observation, and documentation. The selection of respondents was carried out using the snowball sampling technique. The data obtained were analyzed using the Creswell model. To ensure the validity of the data, this study applies the criteria of credibility, transferability, dependability, and confirmability. The results of the study indicate that the principal applies various leadership strategies, such as providing role models, practicing instructional leadership, and empowering teachers in improving the quality of education.